First applications of a targeted exome sequencing approach in fetuses with ultrasound abnormalities reveals an important fraction of cases with associated gene defects - Pangalos, Constantinos (PeerJ, 2016)
Background. Fetal malformations and other structural abnormalities are relatively frequent findings in the course of routine prenatal ultrasonographic examination. Due to their considerable genetic and clinical heterogeneity, the underlying genetic cause is often elusive and the resulting inability to provide a precise diagnosis precludes proper reproductive and fetal risk assessment. We report the development and first applications of an expanded exome sequencing-based test, coupled to a bioinformatics-driven prioritization algorithm, targeting gene disorders presenting with abnormal prenatal ultrasound findings. Methods. We applied the testing strategy to14 euploid fetuses, from 11 on-going pregnancies and three products of abortion, all with various abnormalities or malformations detected through prenatal ultrasound examination. Whole exome sequencing (WES) was followed by variant prioritization, utilizing a custom analysis pipeline (Fetalis algorithm), targeting 758 genes associated with genetic disorders which may present with abnormal fetal ultrasound findings. Results. A definitive or highly-likely diagnosis was made in 6 of 14 cases (43%), of which 3 were abortuses (Ellis-van Creveld syndrome, Ehlers-Danlos syndrome and Nemaline myopathy 2) and 3 involved on-going pregnancies (Citrullinemia, Noonan syndrome, PROKR2-related Kallmann syndrome). In the remaining eight on-going pregnancy cases (57%), a ZIC1 variant of unknown clinical significance was detected in one case, while in seven cases testing did not reveal any pathogenic variant(s). Pregnancies were followed-up to birth, resulting in one neonate harboring the PROKR2 mutation, presenting with isolated minor structural cardiac abnormalities, and in seven apparently healthy neonates. Discussion. The expanded targeted exome sequencing-based approach described herein (Fetalis), provides strong evidence suggesting a definite and beneficial increase in our diagnostic capabilities in prenatal diagnosis of otherwise chromosomally balanced fetuses with troubling ultrasound abnormalities. Furthermore, the proposed targeted exome sequencing strategy, designed primarily as a diagnostic rather than a research discovery tool, overcomes many of the problems and limitations associated with clinical wide-scale WES testing in a prenatal setting.